Inflammatory features of frontal fibrosing alopecia. (1st June 2017) - Ma, Sophia A.; Imadojemu, Sotonye; Beer, Kenneth; Seykora, John T.
Abstract : Introduction: Frontal fibrosing alopecia (FFA) is a cicatricial alopecia typically occurring in postmenopausal women. The etiology and pathophysiology of FFA is poorly understood but thought to be immune mediated. This study aims to further explore the extent of fibrosis and the inflammatory microenvironment by characterizing Langerhans cells (LCs), helper T cells, cytotoxic T cells and B cells near hair follicles in FFA. Methods: Eleven paraffin‐embedded tissues from patients with a clinical and histopathologic diagnosis of FFA were selected for immunohistochemical studies using CD3, CD4, CD8, CD1a and CD20. The lymphocytes and LCs were counted around involved follicles. The CD4/CD8 T‐lymphocyte ratios were calculated and compared to the CD4/CD8 T‐lymphocyte ratios in uninvolved areas. Results: On histopathologic review, at least 35% of follicles in each case were affected by the disease with concentric perifollicular fibrosis and a perifollicular lichenoid lymphocytic infiltrate around the infundibuloisthmic portion of the hair follicle. There was an increase of perifollicular LCs (mean of 18, SD of 5.5) and intrafollicular LCs (mean of 14, SD of 4.3) in involved follicles compared to uninvolved follicles ( P < .0001). The involved follicles also showed a relative decrease in the CD4/CD8 ratio indicating increased numbers of CD8+ T cells; a finding distinct from the CD4‐predominant population in uninvolved follicles ( P < .0001). Conclusion: The inflammatory features of FFA show a CD8‐biased T‐cell infiltrate with increased numbers of LCs in the infundibuloisthmic region. The increased LCs may represent an aberrant immune reaction promoting a CD8+ T‐cell response.